PENGUATAN KAPASITAS MANAJERIAL PELAKU USAHA KREATIF LOKAL MELALUI PELATIHAN DAN MENTORING - Yohan Purnawan; Hendri Mayanta; Benny Sofian Pandinata Purba (Yayasan Nusantara Hasana Berdikari, 2024)
This community service program (PkM) aims to strengthen the managerial capacity of local creative entrepreneurs through structured training and mentoring assistance, enabling them to improve business performance in a measurable manner. Common challenges faced by partners include unorganized financial record-keeping, pricing that is not based on cost of goods sold (COGS), inconsistent digital marketing practices, weak operational and inventory management, and the absence of clear business targets and work plans. The program is implemented through baseline assessment, core training (finance, marketing, operations, human resources, and legal aspects), business clinics, individual and group mentoring, and pre–post evaluation. The outputs include individual business action plans, simple bookkeeping templates, COGS and pricing calculators, concise operational SOPs, and a basic KPI dashboard. The expected impact is an improvement in managerial literacy, better business practices, and increased revenue and efficiency during the post-mentoring period.